Construction progress reporting methods and project outcomes - Ngomana, Ntsako (My University, 2018)
The construction industry is commonly known for project delays and cost overruns in various parts of the world. Developing countries such as South Africa have experienced their fair share of these negative outcomes as outlined in existing literature. The causative factors identified, which relate to poor construction project management, include poor project control and poor progress monitoring and reporting by building contractors. This research was aimed at determining and evaluating the effectiveness of current progress monitoring and reporting methods and their linkage with undesirable project outcomes. The research methodological approach was essentially phenomenological, using a review of relevant literature, which was complemented with a phased field investigation. The field investigation used a mix of both quantitative and qualitative data. Semi-structured interviews were conducted for qualitative data and a survey by questionnaire was used for quantitative data collection. The data was collected from professionals working in the greater Johannesburg area, and hence, the findings could be interpreted to only affect construction projects in Johannesburg; while limiting the generalizability to the Construction industry in South Africa. Therefore, in regulating the impact of the limitation, the sources from which data was collected, intentionally consisted of experienced professionals who have worked on different types of projects of varying complexities. Results from the 80 questionnaire surveys and 15 interviews suggest the existence of appreciable gaps in the accuracy, or quality, in the monitoring and reporting of construction projects progress. Furthermore, the findings revealed that construction inexperience, the lack in project information and the poor allocation of project resources, were perceived to be the most influential factors of undesirable project outcomes. Therefore, the results from this study can be used as a guideline for construction stakeholders to ascertain the importance of implementing adequate progress monitoring and reporting systems to improve poor project outcomes. Building contractors can also use the findings from this study to evaluate their current projects and check the most influential causes of negative outcomes, and how these can be remedied.
A research report submitted in partial fulfilment to the degree of Master in Project Management to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2018
Keywords: Construction industry; Building materials; Sustainable buildings--Design and construction